2018
DOI: 10.11118/actaun201866010253
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education on Economic Growth: The Case of India

Abstract: There exists an enormous interest in clarification of the relationship between education and economic growth. Over the past 30 years, there have been conducted studies by economists about the connection between education and economic growth. There are actually many publications which provide strong evidence that suggests a correlation between the two. This paper attempts to build upon previous publications and to introduce a unique insight along with contemporary evidence about the relationship between educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 20 publications
5
21
0
5
Order By: Relevance
“…The study reveals a positive influence of government expenditure on economic growth in most of the selected countries under the study. Çetintaş and Bağdigen [27] [29] introduced a unique insight along with contemporary evidence about the relationship between education and economic growth in India from 1975 to 2016 by focusing on primary, secondary and tertiary levels of education. The findings of the work show that there is compelling evidence proving a positive connection between education levels and economic growth in India which might influence governmental actions and shape the future of India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study reveals a positive influence of government expenditure on economic growth in most of the selected countries under the study. Çetintaş and Bağdigen [27] [29] introduced a unique insight along with contemporary evidence about the relationship between education and economic growth in India from 1975 to 2016 by focusing on primary, secondary and tertiary levels of education. The findings of the work show that there is compelling evidence proving a positive connection between education levels and economic growth in India which might influence governmental actions and shape the future of India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is believed that education is a poverty alleviation tool, however, Omodero (2019) study on the effect of government sectoral expenditure on poverty lessening in Nigeria, found evidence that government expenses on education and other major economic sectors did not have material influence on poverty reduction agenda. Kotaskova et al (2018) examined the relationship between education and economic growth in India from1975 to 2016 using Granger Causality and Co-integration methods. The study concentrated in primary, secondary and tertiary levels of education and found the existence of a positive link between different levels of education and economic growth in India.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…It is observed that a higher importance attached to training, lead to its greater impact on a nation's fiscal progress (Kotaskova, Prochazka, Smutka, Maitah, Kuzmenko, Kopecka & Honig, 2018). Education is regarded as exceptionally substantial constituent of economic expansion (Ali & Jabeen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Human resources quality has a critical role in a country. The quality of human resources is proven to affect a country (Kotásková, et al, 2018). Countries with good quality human resources tend to have the right level of the economy, and vice versa, countries with lowquality human resources tend to have a lower economic level.…”
Section: Introductionmentioning
confidence: 99%